Conceptuality and Pragmatic Variation in Eighteenth-Century Dutch: The Distribution of the Genitive Case and its Competitors. (2nd September 2018) - Scott, Alan K.
ABSTRACT: This article explores the influence of conceptuality on the distribution of four semantically equivalent possession-marking constructions in eighteenth-century Dutch: the prestigious genitive case (which was promoted in the prescribed norm but was decreasing in productivity at the time), as well as the (relatively) novel van -construction, possessive - s and periphrastic possessive. Comparing the division of labour between these constructions in private egodocuments and texts that were produced for publication, and viewing the findings in the context of contemporary language users' everyday lives, the article reveals and analyses a complex picture of pragmatic variation. Even in the most norm-accordant texts, the prescribed genitive is never dominant. The egodocuments, which did not adhere strictly to the norm, display not only a productive use of the genitive, but also a noticeable rarity of the conceptually oral periphrastic possessive construction. This is attributed to the writers' schooling and their familiarity with the written norm. It is concluded that conceptuality alone was not decisive in eighteenth-century language use, but also the mediality of the communication.